2011
DOI: 10.1099/jmm.0.024497-0
|View full text |Cite
|
Sign up to set email alerts
|

Bullous cellulitis in cirrhotic patients – a rare but life-threatening infection caused by non-O1, non-O139 Vibrio cholerae bacteraemia

Abstract: Bullous cellulitis in cirrhotic patients -a rare but life-threatening infection caused by non-O1, non-O139 Vibrio cholerae

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 9 publications
0
5
0
Order By: Relevance
“…However, among the V. cholerae species, V. cholerae non-O1/O139 strains, which do not secrete the cholera toxin, can cause symptoms similar to as V. vulnificus , especially in patients with liver cirrhosis or immunodeficiency, leading to poor prognosis. [ 3 4 6 7 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, among the V. cholerae species, V. cholerae non-O1/O139 strains, which do not secrete the cholera toxin, can cause symptoms similar to as V. vulnificus , especially in patients with liver cirrhosis or immunodeficiency, leading to poor prognosis. [ 3 4 6 7 ].…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, V. cholerae non-O1/O139 strains do not produce cholera toxins, and their significance has been usually overlooked thus far. However, recent reports have shown that non-O1/O139 strains can cause fatal extraintestinal infections [ 3 4 ]; thus, the clinical importance of these strains is increasing. The mortality rate associated with V. cholerae non-O1/O139 bacteremia has been shown to depend on the studied cohort, and varies from 24% to 61.5% [ 5 ].…”
Section: Introductionmentioning
confidence: 99%
“…In vitro studies have shown a synergistic bactericidal effect when cefotaxime and minocycline were combined (Chuang et al , 1997). Yang et al (2011) reported that 62.5 % of patients treated with a combination of tetracycline and a fluoroquinolone for non-O1/non-O139 V. cholerae sepsis survived, therefore, making it reasonable to administer combination therapy for severe infections. Detection of Vibrio spp.…”
Section: Discussion and Overview Of Available Literaturementioning
confidence: 99%
“…Reference checking resulted in identification of two additional unique articles. Of the 165 retrieved articles, 77 were excluded based on title or abstract, leaving 88 articles including 82 case reports and six articles reporting case series [90][91][92][93][94][95].…”
Section: Reviewmentioning
confidence: 99%